PPAT Responsibilities for Custody of BPHTB Payments in Karanganyar Regency - Aritasari, Nanik (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
Payment of BPHTB tax (Land and Building Rights Acquisition Fee) in Karanganyar is very open with the assistance of the PPAT (Land Deed Official) who is the recipient of the custody of BPHTB tax payments. The community entrusts BPHTB taxes to PPAT due to the lack of tax literacy related to the method of calculation and payment procedures. This phenomenon raises the question, what is the legal responsibility of a PPAT who receives BPHTB tax deposits. Then, what is the procedure for depositing BPHTB taxes with PPAT. This study is a normative-empirical legal research with descriptive analysis. This research has concluded that the deposit of BPHTB tax payments to PPAT does not yet have legality in statutory regulations or the code of ethics of the notarial profession. PPAT has legal responsibility for carrying out tax payment deposit procedures. Violations or negligence in the process of collecting, reporting or depositing BPHTB can result in criminal, civil, administrative or code of ethics sanctions against PPAT. The stages of the procedure for depositing BPHTB tax payments by PPAT in Karanganyar Regency are: (a) the Taxpayer (client) submits an application to the PPAT; (b) The taxpayer provides a power of attorney to the PPAT to entrust BPHTB tax payments; (c) PPAT performs BPHTB calculations based on information on selling and buying prices from the client; (d) Form filling and document checking as a condition for paying BPHTB taxes to the BKD Karanganyar; (e) BPHTB payments through mechanisms in online portals; (f) Payment verification; (g) PPAT makes a deed; (h) PPAT submits documents to BPN for certificate numbering. Keywords: Accountability; BPHTB; Legal; PPAT.